211k views
5 votes
Sandra graphed the system of equations that can be used to solve x^3-2x^2-11x+12=x^3-13x-12 What are the roots of the polynomial equation?

A.) –12, 12

B.) –4, 3

C.) –3, 4

D.) –1, 1

User Cucuru
by
5.5k points

2 Answers

2 votes
First you need to solve the equation for x so it would become -2x^2+2x+24=0, when you factor it out it becomes -2(x^2-x-12)After factoring the inside it becomes -2(x-4)(x+3). Now (x-4) equals to 0 and (x+3) equals to 0 after solving for x you get the roots 4,-3
User IrfanM
by
5.3k points
3 votes

Answer: C.) –3, 4.


Step-by-step explanation: Given equation
x^3-2x^2-11x+12=x^3-13x-12.

Subtracting x^3 from both sides, we get


x^3-x^3-2x^2-11x+12=x^3-x^3-13x-12.


-2x^2-11x+12=-13x-12.

Adding 13x and 12 on both sides, we get


-2x^2-11x+12+13x+12=-13x-12+13x+12.


-2x^2+2x+24=0.

Dividing whole equation by -2, we get


x^2-x-12=0.

Factoring quadratic, we get


(x-4)(x+3)=0.

x-4=0 and x+3=0

x=4 and x=-3.

User Pengyy
by
5.7k points